The commercial law, the Lima Consulate Court, and the organization of the Peruvian Chamber of Commerce in the process of independent Peru - Morales Cerón, Carlos (2024)
The purpose of this article is to describe the historical path of the Lima Consulate Court, between the history of maritime mercantile law and the politics of the nascent Peruvian Republic, as well as the antecedent of the independent Chamber of Commerce of Peru. The first part of the paper is concerned with explaining how maritime mercantile law developed and the contribution of Antonio de Capmany to the discipline of legal history in the context of the emergence of the Consulate Courts. Then, the second part deals with a comparative study of the fortresses of Real Felipe and San Juan de Ulúa, in order to explain that the Spanish Crown not only took possession of normative bodies, but also of fortresses, that is, maritime infrastructure that resists the attacks of corsairs and pirates. Finally, it explains the process of integration of colonial and republican history, represented by the loyalty of the Lima Consulate Court to the royalist forces and how the advent of the Republic meant that the Consulate had to adapt to the new political-administrative regime of independence, which resulted in the creation of the Peruvian Chamber of Commerce.